Mastering JavaScript explore and master modern JavaScript techniques in order to build large-scale web applications - Antani, Ved (Packt Publishing, 2016)
Annotation
Includes index. - Online resource; title from cover (Safari, viewed February 12, 2016)
Keywords: JavaScript (Computer program language); Web applications; JavaScript (Langage de programmation); Applications Web; COMPUTERS; Programming Languages; JavaScript